Quantification of Phenolic Compounds and Carotenoids in a New Cauliflower Variety: Implications for Antioxidant Potential and Nutritional Breeding - Neil Patrick Uy; Hak-Dong Lee; Ju-ri Choi; Sanghyun Lee (Agriculture)
Cauliflower (Brassica oleracea) is a highly nutritious cruciferous vegetable that has garnered increasing attention owing to its potential health benefits. This study aimed to quantify the phytochemical constituents of the new cauliflower variety “BetaCaulie” using advanced analytical methods to elucidate their potential contribution to human nutrition and health. Sinigrin (1), neochlorogenic acid (2), cryptochlorogenic acid (3), and sinapic acid (4) were abundant in the yellow variety, where their concentration reached a total content of 11.86 mg/g. Among the carotenoids, β-carotene (7) had a concentration of 210.77 mg/g. In the DPPH and ABTS+ assays, the control variety exhibited superior antioxidant activity despite having less diverse polyphenols, as evidenced by lower IC50 values of 20.67 and 24.34 mg/mL, respectively. This may be due to the high neochlorogenic acid (2) (14.89 mg/g) content of the control variety. These findings highlight the complexity of plant antioxidant mechanisms, in which different compounds interact uniquely, resulting in an overall antioxidant potential. This dichotomy highlights the potential for targeted breeding strategies that optimize polyphenol or carotenoid levels, depending on the desired health benefits or nutritional goals.